Análisis de los principales elementos de la sentencia de la Corte Internacional de Justicia en el caso de la controversia marítima (Perú c. Chile) a la luz de las posiciones de las partes - Moscoso de la Cuba, Pablo (2014)
On January 27, 2014 the International Court of Justice, principal judicial organ of the United Nations ruled in the case of the maritime dispute (Peru v. Chile), being Peru the one that brought forth the case in January 2008. During the proceedings in Court, the parties presented fundamentally different positions on the existence of a maritime boundary between them and how the Court should proceed solving the dispute. The Court should have considered the multiple legal reasonings presented by the States parties over the years to arrive to its ruling. Particularly, some of the legal reasonings presented by Peru were accepted by the Court and considered in the ruling, beginning from the interpretation given to the proclamations of Peru and Chile in 1947, going through the reasonings Peru presented about the 1952 Santiago Declaration (It was the main topic presented by Chile, which was discarded by the Court) until the reasoning presented by Peru saying that the 1954 Special Maritime Frontier Zone Agreement didn’t create a zone of tolerance that extends to 200 nautical miles. However, the Court considered that in the 1954 agreement the parties accepted the existence of a tacit agreement, but this existence was not presented by them in the Court even though it has a legal support in the jurisprudence of the International Court of Justice. Then, the Court had to determine the extent of the tacit agreement, a very difficult duty because the parties hadn’t considered the existence of that situation and its extension. After establishing the implied legal agreement was for 80 nautical miles along a parallel of latitude, the Court proceeded to establish a maritime boundary applying thoroughly the rules and principles of maritime delimitation presented by Peru, which applied to the case determine the presence of an equidistant line. In relation to the starting-point of the maritime boundary, the Court didn’t use the point presented by Peru but, in a correct way, made it clear that the starting-point of the maritime boundary and the starting-point of the land boundary don’t have to match necessarily. Finally, the way how the Court established the maritime boundary recognizes, with no doubt, that the area previously named “outer triangle” belongs to Peru, as this country claimed and as Chile opposed repeatedly over the years. In summary, it is a decision based on International Law and adopted under the evidence presented in Court. The Court applied and confirmed various legal arguments presented by Peru during the process, in spite of the opposing position of Chile.